2021
DOI: 10.1101/2021.09.01.458544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 spike (S) and the orthoreovirus p15 cause neuronal and glial fusion

Abstract: Numerous enveloped viruses use specialized surface molecules called fusogens to enter host cells. During virus replication, these fusogens decorate the host cells membrane enabling them the ability to fuse with neighboring cells, forming syncytia that the viruses use to propagate while evading the immune system. Many of these viruses, including the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), infect the brain and may cause serious neurological symptoms through mechanisms which remain poorly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…In this study, we generated hCOs using a previously published protocol [ 1 , 42 ] and demonstrated the potential of AAV for gene delivery. Across independently produced batches, hCOs showed reproducibility in all parameters measured including size, neuronal cell type markers, gene expression profile, and neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we generated hCOs using a previously published protocol [ 1 , 42 ] and demonstrated the potential of AAV for gene delivery. Across independently produced batches, hCOs showed reproducibility in all parameters measured including size, neuronal cell type markers, gene expression profile, and neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the invasion of SARS-CoV-2 into the brain might cause severe effects on brains, because only spike protein without replicating virus can cause syncytia which could cause apoptosis and cell death [54,55]. Moreover, human brain organoids and nervon cells expressing spike protein could lead to the formation of syncytia [56]. SARS-CoV-2-indcued fusion was correlated with the neurodegenerative disorders [50].…”
Section: Effects Of Sars-cov-2-mediated Syncytiamentioning
confidence: 99%
“…myocardial injury and thrombosis), and mortalities have been reported in relation to vaccination (28)(29)(30)(31). Although some side effects may stem from the delivery modalities, several studies have indicated that the spike protein alone causes adverse effects on host tissues, such as blood brain barrier disruption, neuron fusion, inflammation, and cell senescence (32)(33)(34)(35). Although it is difficult to detect the origin of side effects in vaccinated individuals, more investigation on the cellular effects of mRNA vaccines or the expressed protein antigen are warranted to create safer vaccines.…”
Section: Introductionmentioning
confidence: 99%